ChemInform Abstract: Sodium Carbonate Mediated Regioselective Synthesis of Novel N‐(Hydroxyalkyl)cinnamamides. Issue 17 (28th April 2014) - Garg, Parul; Milton, Marilyn Daisy
Abstract A direct and efficient amidation of cinnamic methyl esters with aminoalcohols is developed in the presence of sodium carbonate as the base.